Donors and archives : a guidebook for successful programs - Purcell, Aaron D., 1972- (Lanham : Rowman and Littlefield, 2015)
"Donors and Archives: A Guidebook for Successful Programs highlights the importance of development and fundraising for archives, while focusing on the donor and potential donor. Their interest, their support, their enthusiasm, and their stuff are vital to the success of archival programs. Archivists involved in donor work and fundraising will find the practical advice and best practices in this book applicable, replicable, timely, and valuable"--
Introduction -- PART I. THE PLANNING -- Donor preparedness and the archival program -- Archival obligations and shared expectations -- Developing donor strategies -- PART II. THE PROCESS -- Negotiating and reviewing a potential donation -- The details of a donation -- The days following a donation -- PART III. THE PARTNERS -- Donor types -- The development office and the archives -- Friends, lovers, and supporters of archives -- PART IV. THE PAYOFF -- The value of a donor program.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Master record variable field(s) change: 072 - OCLC control number change
Keywords: Archives -- Collection management -- Handbooks, manuals, etc; Archival materials -- Collectors and collecting -- Handbooks, manuals, etc; Manuscripts -- Collectors and collecting -- Handbooks, manuals, etc; Appraisal of archival materials -- Handbooks, manuals, etc; Archives -- Public relations; Fund raising; Benefactors; Gifts; LANGUAGE ARTS & DISCIPLINES -- Library & Information Science -- General; Appraisal of archival materials; Archives -- Collection management; Archives -- Public relations; Benefactors; Fund raising; Gifts; Manuscripts -- Collectors and collecting; Electronic books; Handbooks and manuals